Fikih Perlawanan Kolonialisme Ahmad Rifa’i - Dahrul Muftadin (JURNAL PENELITIAN, 2017)
This paper aims to trace the thought of Fiqh K.H. Ahmad Rifai as a form of protest against Dutch colonialism, which resulted in the suffering of people in various regions. Through a qualitative approach, by collecting data from various sources—both literature and interviews with witnesses of history, this study concludes that the resulting fiqh product is oriented toward resistance against the colonial government, which is considered to be kafir. People who support the colonial government are labeled as ungodly; therefore, it is considered illegal for them to serve as prayer imams as well as to conduct marriages.